Further refinements of Jensen's type inequalities for the function defined on the rectangle - Khan, Muhammad Adil; Khan, Gulzar Ali; Ali, Tahir; Batbold, Tserendorj; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
We give refinement of Jensen's type inequalities given by Bakula and Pečarić (2006) for the co-ordinate convex function. Also we establish improvement of Jensen's inequality for the convex function of two variables.